MEMBACA NARASI DOSA AKHAN DARI POTRET KAUM PENTAKOSTAL - Kosma Manurung (Jurnal Missio Cristo, 2023)
Both in the past and today, sin still has a bad impact on human life. The narrative of Achan's sin, which is used as the main study of this research, for example, shows that sin easily entered through Achan's inability to overcome his desire to own the spoils that so attracted his attention, and were of high value economically as well as awe. This then triggers Achan to dare to go against God's commandments. This action that Achan took, not only damaged Achan's life personally, but also resulted in the death of thirty-six Israeli soldiers who attacked the city of Ai and made Achan, his children, receive God's punishment for his actions. This article intends to read the narrative of Achan's sin from the Pentacpstals portrait. Hopely, use of the narrative interpretation method and literature review will provide a thorough and coherent description of the narrative of the conquest of Jericho by the Israelites, the narrative interpretation of Achan's sin, as well as portraits of the Pentecostals regarding this story. In conclusion, the Pentecostals portray this narrative of Achan's sin as God's attitude that never compromises with sin, do not underestimate God's commands, every action has its consequences, and the importance of always connecting oneself to God's promises. ABSTRAK BAHASA INDONESIA Baik itu di masa lalu maupun hari ini, dosa masih membawa dampak buruk dalam kehidupan manusia. Narasi dosa Akhan yang dijadikan kajian utama penelitian ini contohnya, memperlihatkan bahwa dengan mudah dosa masuk melalui ketidakmampuan Akhan mengalahkan keinginannya memiliki barang rampasan yang begitu menarik perhatiannya, serta bernilai tinggi secara ekonomi maupun juga rasa kagum. Hal ini kemudian memicu Akhan untuk berani melawan perintah Allah. Tindakan yang Akhan lakukan ini, bukan sekedar merusak kehidupan Akhan secara pribadi, melainkan juga berdampak pada tewasnya tiga puluh enam prajurit Israel yang menyerang kota Ai serta membuat Akhan, anak-anaknya mendapatkan hukuman Allah karena tindakannya. Artikel ini bermaksud membaca narasi dosa Akhan dari potret kaum Pentakostal. Adapun Penggunaan metode tafsir naratif serta kajian literatur diharapkan mampu memberi gambaran yang runut dan lebih teliti perihal narasi penaklukan Yerikho oleh bangsa Israel, tafsir naratif dosa Akhan, serta potret kaum Pentakostal terkait kisah ini. Disimpulkan, kaum Pentakostal memotret narasi dosa Akhan ini sebagai sikap Allah yang tidak pernah kompromi dengan dosa, jangan memandang remeh perintah Allah, setiap tindakan memiliki konsekuensinya, serta pentingnya selalu mengkoneksikan diri pada janji Allah.